(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2025)
Primary school science education plays a pivotal role in igniting children’s scientific curiosity. This formal education can be enriched by activities developed from university extension and awaken a passion for science from an early age. As part of an initiative, we implemented two Natural Science workshops in six rural schools in San Luis, Argentina. These workshops combined informative talks with practical activities, such as the use of magnifying glasses and microscopes, generating great interest and enthusiasm among the students. The experience was positive for both the students and the future educators involved, highlighting the role of university outreach in bringing science to rural communities and contributing to the holistic education of future citizens. The need to continue working to improve the quality of science education at all levels is emphasized.